The Impact of Green Innovation on Business Sustainability A Case Study of SMEs - Hindarsah, Ida; Fauzi, Teddy Hikmat; Fachrudin, Adi; Ali, Khan Sarfaraz (International Journal of Science and Society, 2025)
Micro, Small, and Medium Enterprises (MSMEs) can be an alternative for the government to increase the country's economic productivity. This enormous economic potential cannot be separated from existing challenges, such as adapting sustainable business practices. This study aims to analyze the relationship between green innovation and business sustainability. Using a quantitative approach, data was collected through questionnaires distributed to 64 knitting and weaving MSMEs in Bandung Regency. The data was analyzed using the Structural Equation Modelling - Partial Least Squares (SEM-PLS) method. The results of the analysis show that Green Innovation has a significant positive effect on Business Sustainability, where 58.5% of the variance in Business Sustainability can be explained by Green Innovation. Based on these findings, it can be concluded that Green Innovation has a significant positive effect on Business Sustainability.